Analysis of Students' Spatial Abilities Reviewed From Gender Differences In Class X - Telaumbanua, Esterni; Ratumanan, Tanwey Gerson; Silitonga, Rhyanti (Universitas Wiralodra, 2024)
Spatial skills are important for studying geometric shapes. People who have good spatial abilities can easily imagine objects in three dimensions. Factors that influence differences in student abilities include gender differences. The aim of this research is to describe students' spatial abilities in terms of gender differences. The type of research used is quantitative-qualitative research. Spatial ability test results data are calculated and presented in quantitative form and analyzed qualitatively. This research was conducted at SMA Negeri 3 Ambon class X Science 1 with a total of 36 students consisting of 12 male students and 24 female students. In determining the subject of this research, a purposive sampling technique was used, namely taking data sources with certain considerations. The research subjects selected to be interviewed were 6 students with the assessment criteria for spatial ability test questions consisting of 1 male student and 1 female student with high spatial ability, 1 male student and 1 female student with moderate spatial ability, and 1 male student with moderate spatial ability. male and 1 female student with low spatial abilities. The largest percentage of student test results are in the low category. Based on the results of the spatial ability test, it shows that in the element of spatial perception, male subjects are more likely to meet the indicators of the ability to identify objects vertically and horizontally even though the position of the object is manipulated. Meanwhile, female subjects tend to use their spatial abilities as indicators of the ability to distinguish lines, horizontal and vertical planes in spatial figures. In the spatial visualization element, male subjects are more likely to fulfill the indicators than female subjects regarding stacks of unit cubes whose position or shape has been manipulated and visualizing stacks of unit cubes from more than one point of view. For the element of mental rotation, male subjects tend to be more capable than female subjects of rotating, imagining rotation and describing a flat shape or spatial structure correctly after rotation. However, elements of spatial orientation of female subjects are more likely to determine the appearance of objects from different perspectives than male subjects. In the spatial relations element, male subjects are more likely to determine the relationship of an object with other objects than female subjects.